2019
DOI: 10.1186/s12979-019-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila ameliorates the age-related decline in colonic mucus thickness and attenuates immune activation in accelerated aging Ercc1−/Δ7 mice

Abstract: Background The use of Akkermansia muciniphila as potential therapeutic intervention is receiving increasing attention. Health benefits attributed to this bacterium include an improvement of metabolic disorders and exerting anti-inflammatory effects. The abundance of A. muciniphila is associated with a healthy gut in early mid- and later life. However, the effects of A. muciniphila on a decline in intestinal health dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 57 publications
6
117
0
Order By: Relevance
“…We found that S. pullorum inhibited the production of goblet cells and decreased the expression of Muc2 and Tff2, which caused serious intestinal mucosa damage. It has been previously reported that A. muciniphila can increase mucus thickness and this ability is associated with the secretory function of goblet cells [36]. In our study, treatment with A. muciniphila after damage restored the number of goblet cells, reversing intestinal mucosa damage and increasing the expression of Muc2 and Tff2, which was also confirmed in a previous report [31].…”
Section: Figure 3 a Muciniphila Activates Gut Growth And Increases Tsupporting
confidence: 92%
“…We found that S. pullorum inhibited the production of goblet cells and decreased the expression of Muc2 and Tff2, which caused serious intestinal mucosa damage. It has been previously reported that A. muciniphila can increase mucus thickness and this ability is associated with the secretory function of goblet cells [36]. In our study, treatment with A. muciniphila after damage restored the number of goblet cells, reversing intestinal mucosa damage and increasing the expression of Muc2 and Tff2, which was also confirmed in a previous report [31].…”
Section: Figure 3 a Muciniphila Activates Gut Growth And Increases Tsupporting
confidence: 92%
“…While lentil and common bean induced, respectively, a 49-fold and 25-fold increase in this bacterium relative to the high-fat control diet, chickpea and dry pea had no effect. The relevance of A. muciniphila is that colonization of the gut with this bacterium has been reported to be inversely associated with obesity, diabetes, and inflammation [74][75][76][77][78][79]. The differential effects of pulse consumption on the content of A. muciniphila is consistent with a selective effect limited to lentil and common bean.…”
Section: Discussionmentioning
confidence: 88%
“…16 Importantly, the beneficial effects of the bacteria on cardiometabolic features were thereafter supported by others using various pathological murine models. [17][18][19][20][21][22] Recently, we discovered that pasteurization of the bacteria (i.e., treatment for 30 min at 70°C) made it more effective than the live bacteria in preventing DIO in mice. 23 This finding was recently confirmed in a first proof-of-concept pilot human intervention.…”
Section: Introductionmentioning
confidence: 99%